2006
DOI: 10.1099/vir.0.81625-0
|View full text |Cite
|
Sign up to set email alerts
|

Movement of potexviruses requires species-specific interactions among the cognate triple gene block proteins, as revealed by a trans-complementation assay based on the bamboo mosaic virus satellite RNA-mediated expression system

Abstract: The intra-and intercellular transport of potexviruses require interactions among viral RNA, coat protein and elements of the triple gene block proteins (TGBps). In this study, the requirement of bamboo mosaic virus (BaMV) TGBps for movement functions and the compatibilities with those of two potexviruses, Potato virus X (PVX) and Foxtail mosaic virus (FoMV), were examined using a satellite RNA-mediated trans-complementation assay system. Single or multiple TGBps of BaMV, PVX and FoMV were expressed from BaMV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Being a messenger-type satRNA, satBaMV RNA encodes a P20 gene, which, unlike all other large messenger-type satRNAs, was shown to be nonessential for the replication of satRNA. Therefore, P20 was replaced with a chloramphenicol acetyltransferase (CAT) gene, which resulted in high expression of the CAT protein in infected Chenopodium quinoa and demonstrated that satBaMV RNA could be useful as a satellite-based expression vector.As vectors for functional studies:satBaMV RNA has been used for the expression of individual TGBps in a complementary experiment for study of cell-to-cell movement of BaMV [123]. To dissect the functions of individual TGBps, single or multiple TGBps of BaMV, PVX and Foxtail mosaic virus were expressed by use of satBaMV RNA-based vectors to complement the functions of green fluorescent protein-tagged, movement-defective BaMV with mutation(s) in the matching gene(s).…”
Section: Practical Applications Of Satrnasmentioning
confidence: 99%
“…Being a messenger-type satRNA, satBaMV RNA encodes a P20 gene, which, unlike all other large messenger-type satRNAs, was shown to be nonessential for the replication of satRNA. Therefore, P20 was replaced with a chloramphenicol acetyltransferase (CAT) gene, which resulted in high expression of the CAT protein in infected Chenopodium quinoa and demonstrated that satBaMV RNA could be useful as a satellite-based expression vector.As vectors for functional studies:satBaMV RNA has been used for the expression of individual TGBps in a complementary experiment for study of cell-to-cell movement of BaMV [123]. To dissect the functions of individual TGBps, single or multiple TGBps of BaMV, PVX and Foxtail mosaic virus were expressed by use of satBaMV RNA-based vectors to complement the functions of green fluorescent protein-tagged, movement-defective BaMV with mutation(s) in the matching gene(s).…”
Section: Practical Applications Of Satrnasmentioning
confidence: 99%
“…The mutations of the chloroplast-targeting signal in AltMV TGB3 protein resulted in very limited cell-to-cell movement, suggesting that this signal is required for the systemic movement of AltMV (Lim et al, 2010a). Together, these data indicate that the mechanisms for viral movement may differ among potexviruses (Lin et al, 2006). …”
Section: Intracellular Trafficking Of Potexvirus Vrna From the Cytoplmentioning
confidence: 86%
“…As many positive strand RNA viruses, BaMV must encode its own enzymes for replication/transcription and 5′ cap formation because it replicates only in the cytoplasm. ORF2, 3 and 4 are overlapped, often referred to as the triple gene block (TGB), and their translated proteins, TGBp1, TGBp2, and TGBp3, respectively, are indispensable for BaMV movement in plants (Lin et al, 2004, 2006). In-depth discussions about the functions of each of the TGB proteins of PVX in the intracellular trafficking and intercellular transport can be referred in a couple of recent reviews (Verchot-Lubicz et al, 2010; Park et al, 2014).…”
Section: Bamv Genomementioning
confidence: 99%